Neonatal infection in Sub-Saharan Africa: a cross-sectional pilot study on bacterial pathogens and maternal risk factors - Blumenröder, Simone; Wilson, Damas; Ndaboine, Edgard; Mirambo, Mariam M.; Mushi, Martha F.; Bader, Oliver; Zimmermann, Ortrud; Mshana, Stephen E.; Groß, Uwe (Frontiers in Microbiology, 2023)
Introduction: Although child morbidity and mortality could be reduced in sub-Saharan Africa during the last years both remain high. Since neonatal infections play a major role, we conducted a cross-sectional pilot study in the lake region of Western Tanzania in order to analyse not only the prevalence of neonatal infection with its bacterial aetiology including antimicrobial resistance pattern but also to detect potential maternal risk factors. Methods: We screened 156 women for potential risk factors and examined their neonates for clinical signs of an infection including microbiological verification. All women were interviewed for medical history and their socio-economic background. High vaginal swabs (HVS) of pregnant women and blood cultures of sick infants were investigated for bacterial pathogens using culture followed by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) or polymerase-chain-reaction (PCR)-based assays. Antimicrobial resistances were determined using disc diffusion test and verified by VITEK 2. Maternal malaria, blood glucose and haemoglobin levels were determined by rapid tests and helminths infections by stool microscopy. Results and Discussion: Our results showed a prevalence of 22% for neonatal infections. 57% of them had culture-positive blood stream infection with Gram-negative bacteria being most prevalent. All these expressed resistance against ampicillin. The prevalence of maternal infection with helminths or Plasmodium was low, indicating that anti-worming strategies and intermittent preventive treatment of malaria for pregnant women (IPTp) being effective. The study identified maternal urinary tract infection (UTI) and an elevated blood glucose level as potential maternal risk factors for an early neonatal infection, an elevated blood glucose level and maternal anaemia for a late onset infection. Conclusion: Our study therefore indicates that monitoring maternal UTI in the last trimester as well as levels of maternal haemoglobin and blood glucose might be important to predict and eventually manage neonatal infections. As Gram-negative bacteria with resistance to ampicillin were most prevalent in culture-proven neonatal sepsis, WHO recommendations for calculated antibiosis in the sick young infant should be discussed.